Effectiveness of Tembelekan Leaf Extract (Lantana camara L.) on Mortality of Riptortus linearis - Rulan U. Mustapa; Chairunnisah J. Lamangantjo; Aryati Abdul; Jusna Ahmad; Wirnangsi D. Uno; Yuliana Retnowati (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect, effective concentration, Lethal Concentration 50 (LC50), and Lethal Time (LT50) of tembelekan leaf extract (Lantana camara L.) on the mortality of Riptortus linearis and metabolic compounds of L. camara leaves. The method was experimental. The study used a completely randomized design (CRD) with five treatments, namely 0%, 10%, 15%, 20%, and 25%, and five replications. Each treatment contained 10 R. linearis test animals. The results of the ANOVA analysis showed the effect of treatment on the mortality of R. linearis (p<0.05). The concentration that showed the highest mortality was 25%. Based on the LC50 test, the 10.155% L. camara leaf extract concentration can kill R. linearis in more than 50% of each treatment. And based on LT50 with a concentration of 25%, it takes 7.681 hours to kill 50% of R. linearis. In L. camara leaf extract contains metabolite compounds, namely alkaloids with a level of 307.87 mg/L, then tannins with a group of 2.75 %b/v, then saponins with a group of 0.31 %b/v, and flavonoids with a group of 1.40 %b/v., It can be concluded that there is an influence of giving tembelekan (Lantana camara L) leaf juice on the mortality of Riptortus linearis.